Law and Literature: Reflections on William Shakespeare’s Measure for Measure - Curto, Jorge Christian (Aequitas Virtual, 2023)
The relationship between law and literature is a topic that has been analysed in different essays. Certain authors consider that the latter is a useful instrument to train lawyers. There are novels, short stories and plays which constitute tools to reflect on law. Some plays written by William Shakespeare are suitable to think about different legal aspects. Measure for Measure is about the application and interpretation of law, ethics and morality. Furthermore, it is about political shrewdness. In this article I analyse the play from an interdisciplinary perspective.